Pengembangan Alat Permainan Edukatif Skipping Jump Pelepah Pisang Berbasis Kearifan Rokan Hilir Riau untuk Meningkatkan Motorik Kasar Anak - Juliana, Juliana; Heldanita, Heldanita; Bakhtiar, Nurhasanah; Sariah, Sariah; Murniati, Wahyuni; Abdul Nasir Zakaria, Gamal; Irawan, Yossy (LPPM STAI La Tansa Mashiro, 2025)
This research is motivated by the lack of development of educational game tools based on local wisdom culture in Rokan Hilir. Furthermore, the gross motor development of children at RA Raudhatush Sholihin is also under-stimulated. This study aims to develop an educational game tool Skipping Jump that has educational value in stimulating aspects of gross motor development in early childhood. The research method is a Research and Development (R&D) type development method with the ADDIE model. Data collection techniques use questionnaires, observation, and documentation. Data analysis techniques in the study are using data obtained from validator input at the validation stage, input from media experts and using statistical score calculations obtained from respondents' answers on a Likert scale.The results of this study were obtained based on assessments from media experts with a percentage of 93%, assessments from material experts were obtained at 96%, assessments from principals and teachers were obtained at 87.8%, so that the assessment from the validator questionnaire was categorized as